Nurturing modalities of inquiry in entrepreneurship research : seeing the world through the eyes of those who research - Higgins, David; Brentnall, Catherine; Jones, Paul; McGowan, Pauric (Contemporary issues in entrepreneurship research ;, 2023)
Despite the developing richness of the field of Entrepreneurship research, the output still suffers from a lack of methodological diversity. This edited collection stimulates discussion, shares practice and explores challenges around current and new approaches to inquiry - encompassing all aspects of entrepreneurship research, from its conception through to its execution and related issues such as education, training and learning. Advancing the way, we learn, think about and engage with various modalities of inquiry in Entrepreneurship research and practice, and its related subjects and areas of interest, the chapter authors draw inspiration from leading academics in the subject areas across the field. Their explorations centre around three critical points: the questioning of assumptions - who we are and what it is that we want to achieve; of what really makes sense - how we live and experience, our own and other voices and conversations; and of understanding our relationship with our social world and recognising its dynamic and emergent nature. Contemporary Issues in Entrepreneurship Research is an official book series of the Institute for Small Business and Entrepreneurship (ISBE). Each volume is designed around a specific theme of importance to the entrepreneurship and small business community with articles collectively exploring and developing theory and practice in the field.